Identification of Patients With Schizophrenia: Immediate Action to Control COVID-19 Pandemic in Iran - Mohammad Reza Mousavi; Mahboobeh Besharatpour (Gonabad University of Medical Sciences, 2022)
The characteristics of schizophrenia, including delusions, hallucinations, poor insight, cognitive impairment, and disorganized behavior [1] and demographic characteristics including homelessness and living in communal homes [1] have provided the basis for COVID-19 infection in patients with schizophrenia. Due to impairments in insight and decision-making capacity, people with schizophrenia are less likely to adhere to protective measures [2].